Green building standards and their implementation in Ukraine - Savchenko, Antonina (Видавництво Львівської політехніки, 2024)
Today, one of the most discussed topics among builders is the post-war reconstruction of the country using the principles of green construction. Ever since the conclusion of the Association Agreement with the EU, Ukraine has been actively implementing EU environmental standards into national legislation. The threat posed by the war to the environment resembles an iceberg, because most of the negative consequences are hidden and will manifest themselves decades after the end of the war. That is why right now, we have to make maximum efforts to reduce the negative impact of man and his activities on the surrounding natural environment. Application of environmental standards in construction will make it possible to minimize the impact of the industry. For this purpose, we conduct an analysis of advanced BREEAM, LEED, DGNB systems. Each of the standards has its own characteristics and their application in the conditions of Ukraine has its pros and cons. Standards are one of the tools for the implementation of state policy, belong to the category of “normative document” (ND) and establish uniform rules, requirements, methods of control and testing, marking. Despite the intensive implementation of EU environmental standards in the legislation of Ukraine, there is still no legally established requirement for the certification of buildings according to a specific “green construction” standard. The development of own national standards is a significant step towards the introduction of green building standards in Ukraine.
Keywords: green construction; BREEAM; LEED; DGNB; building certification; implementation of environmental standards